Richard Quinney's The Social Reality of Crime: A Marked Departure from and Reinterpretation of Traditional Criminology - Wozniak, John F. (Social justice, 2014)
The article presents several commentaries on the book "The Social Reality of Crime" by Richard Quinney. Topics include an interpretation of crime as a constructed reality; the ability of power, law and control to determine who and what is criminalized; and the impact of stereotypes about crime and criminals on views about justice.